Development and evaluation of recombinant outer membrane protein i-elisa for diagnosis of caprine brucellosis - Ahmed, Ihsan Muneer (2013)
Brucella melitensis is the main etiological agent of caprine brucellosis. The common serological tests for diagnosis of brucellosis include: Rose Bengal plate test (RBPT), complement fixation test (CFT) and enzyme linked immunosorbent assay (ELISA). These tests usually detect antibodies against smooth lipopolysaccharide (LPS). Therefore, they may give false positive serological reactions (FPSR) due to vaccination with B. melitensis Rev.1 vaccine strain or natural infection by a number of Gram negative bacteria, mainly Yersinia enterocolitica O:9. The insufficiency of the current serological tests to differentiate the goats with FPSR leads to erroneous decision to cull them and resulting in unnecessary loss of animals. The results of previous researches using single recombinant outer membrane protein (rOMP) of Brucella, such as OMP28 or OMP31 showed lack of sensitivity. Therefore, combination of more than one rOMP might improve the sensitivity of the diagnostic test. Accordingly, this study was conducted to develop and evaluate in-house rOMPs I-ELISA based on combination of rOMP25, rOMP28 and rOMP31 to differentiate FPSR using mouse model and goats as the natural host of B. melitensis. The whole cell protein profiles of six B. melitensis field isolates were characterized using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The results revealed overall similarities among these isolates. Therefore, only the goats isolates studied for their OMPs antigenicity by immunoblotting using rabbit serum raised against B. melitensis strain 0331 field isolate. The results confirmed the presence of OMP25, OMP28, and OMP31 as immunogenic protein candidates. Accordingly, the omp25, omp28 and omp31 genes of B. melitensis strain 0331 field isolate were amplified by PCR and cloned using pET-32 Ek/LIC prokaryotic system. The nucleotide sequences of these three genes were successfully submitted to the GenBank. The expression of the omp25, omp28, and omp31 genes were studied in E. coli BL21(DE3). The purified expressed recombinant fusion proteins were analyzed by Western immunoblotting and the results revealed that rOMP25, rOMP28 and rOMP31 fusion proteins were immunogenic and in properly folded form, suggesting their usefulness as antigenic candidates for serological diagnosis of brucellosis. The rOMP25, rOMP28 and rOMP31 were combined and named as rOMPs and used to develop in-house rOMPs I-ELISA which was evaluated using serum samples obtained from three groups of BALB/C mice. Group 1 was infected with B. melitensis strain 0331 field isolate, while group 2 and 3 were vaccinated with B. melitensis Rev.1 vaccine strain, and infected with Y. enterocolitica O:9 respectively. Using RBPT, no significant differences were found in the immune response among the three groups. On the other hand, the in-house rOMPs I-ELISA was able to differentiate the group 1 from FPSR due to either vaccination by B. melitensis Rev. 1 vaccine strain (group 2) or infection by Y. enterocolitica O:9. (group3). The in-house rOMPs I-ELISA was further evaluated using serum samples from four groups. The groups comprised: naturally infected goats with B. melitensis, goats free from Brucella infection, goats vaccinated with B. melitensis Rev. 1 vaccine strain and random field samples from goats with unknown Brucella status. All the sera were tested using the in-house rOMPs I-ELISA, RBPT, BRUCELISA-400SG and CFT. When samples from vaccinated goats were tested, RBPT, BRUCELISA-400SG and CFT categorized these samples as positive. This implies that the common serological tests were not able to differentiate truly infected animals from those vaccinated, while the in-house rOMPs I-ELISA developed was able to differentiate between the vaccinated and infected goats with 94.44% sensitivity and 84.62% specificity. In conclusion, the newly developed in-house rOMPs I-ELISA was able to differentiate vaccinated goats as a cause of FPSR, which indicate that this test has the potential diagnostic abilities over the commonly used tests; hence it can support the diagnosis of caprine brucellosis and potentially save animals from being erroneously culled in testing and culling serosurveillance efforts.